Global University Rankings in the Polish Context: the University of Warsaw, a Case Study - Kwiek, Marek (My University, 2016)
University rankings are a topic of controversy and contention in many countries. Poland is no exception. This chapter analyzes aspects of rankings in the Polish context. Poland is a particularly interesting case, since it is a middle-sized country with a middle-tier higher education system. Among the questions discussed here are: what is the impact of global university rankings on the Polish national flagship university, the University of Warsaw? Are the changes in funding and governance occurring in Polish higher education, and in our case study institution, directly or indirectly linked to rankings? Are rankings driving the push for planned changes both in the system and in the case study institution, or do these developments merely happen to be concurrent? How do academics and administrators view global rankings? What are their perceptions of global rankings with reference to the institution and to their own academic careers? How, if at all, do global rankings relate to national rankings? Is the institutional culture of the case study university changing more due to ongoing reforms, global rankings, or national rankings? These questions are discussed in a context of ongoing higher education reforms, rooted in the OECD discourse of the increasing role of competition in research and of competitive research funding in higher education funding.
Keywords: University of Warsaw; global rankings; university rankings; national rankings; Polish higher education; flagship university; semi-structured interviews; qualitative methods; Polish universities; academic profession; higher education reforms